Type II hybrid arch repair versus total arch replacement with frozen elephant trunk: a propensity score-matched analysis. (10th April 2021) - Liu, Yanxiang; Liang, Shenghua; Zhang, Bowen; Dun, Yaojun; Guo, Hongwei; Qian, Xiangyang; Yu, Cuntao; Sun, Xiaogang
Abstract: : OBJECTIVES: The aim of this study was to evaluate the objective outcomes of type II hybrid arch repair (HAR) and total arch replacement with frozen elephant trunk (TAR with FET). METHODS: Data from 528 patients who underwent aortic arch repair from January 2017 to June 2019 were collected, which consisted of 175 type II HAR and 353 TAR with FET. The propensity score-matched analysis identified a subgroup of 90 pairs. Perioperative data and mid-term follow-up results were assessed. RESULTS: There was no significant difference in the composite adverse events (type II HAR, 20.6%, 36/175 vs TAR with FET, 17.8%, 63/353, P = 0.450). Multivariable logistic analysis of the 528 patients showed that the procedure type (type II HAR or TAR with FET) was not associated with composite adverse events, 30-day mortality or stroke. The 3-year survival rates were 84.8% in the type II HAR group and 90.1% in the TAR with FET group ( P = 0.12). The 3-year reintervention-free rates in the type II HAR and TAR with FET groups were 98.7% and 96.5% ( P = 0.22), respectively. After matching, no significant difference was found in the incidence of composite adverse events or the 3-year survival and reintervention-free rates. CONCLUSIONS: No significant clinical differences were found in the early and mid-term outcomes of type II HAR and TAR with FET. The long-term outcomes remain to be investigated. Careful patient selection for individualized approaches is the key to taking full advantage of the 2 surgical procedures.